Parliaments in Europe Engaging in Post-legislative Scrutiny - Elena Griglio; Nicola Lupo (Journal of Southeast Asian Human Rights, 2020)
Post-legislative scrutiny (PLS) is not completely new to European parliamentarism. In the last few decades, this activity has experienced rapid development, either pushed by supranational trends on better regulation or fostered by national constitutional reforms. However, the involvement of parliaments in the ex post stage of law-making still remains under-theorised. This article aims at providing a comparative overview of the main rules, practices and trends on post-legislative scrutiny in Europe, focusing on the experience of three bicameral Parliaments: the French, Italian and Swiss Parliaments which have been selected as examples of three proactive approaches to post-legislative scrutiny, based on alternative bicameral arrangements. After providing a general overview of the main options that support the involvement of parliaments in the ex-post stage of law-making, the article examines how the benchmark case studies address the following variables: the internal organisation of the ex-post scrutiny, including the role of the administrative staff; the scrutiny object, either referred to single pieces of legislation or to a whole policy; the scope of the ex-post scrutiny, verifying whether it is interpreted as a purely legal dimension or it comprises also forms of impact assessment; the outcomes of the ex-post scrutiny, and more specifically its contribution to the legislative decision-making. The paper demonstrates that PLS in parliament may lead to political outcomes addressing the government when the form of government, the constitutional framework and the party dimension support a competitive use of this tool in the legislative-executive interaction.